2018
DOI: 10.1098/rstb.2017.0032
|View full text |Cite
|
Sign up to set email alerts
|

Can we use mice to study schizophrenia?

Abstract: The validity of rodent models for the study of psychiatric disorders is controversial. Despite great efforts from academic institutions and pharmaceutical companies, as of today, no major therapeutic intervention has been developed for the treatment of psychiatric disorders based on mechanistic insights from rodent models. Here, we argue that despite these historical shortcomings, rodent studies are nevertheless instrumental for identifying neuronal circuit mechanisms underlying behaviours that are affected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Thus, stressed Mmp-9 heterozygous mice might serve as a useful model of the deficit type of schizophrenia. However, caution must be taken when considering the reliability of animal models of schizophrenia (Powell and Miyakawa, 2006; Nestler and Hyman, 2010; Young et al, 2010; Jones et al, 2011; Canetta and Kellendonk, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, stressed Mmp-9 heterozygous mice might serve as a useful model of the deficit type of schizophrenia. However, caution must be taken when considering the reliability of animal models of schizophrenia (Powell and Miyakawa, 2006; Nestler and Hyman, 2010; Young et al, 2010; Jones et al, 2011; Canetta and Kellendonk, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The utility of mouse or other animal models of schizophrenia has been debated (Powell and Miyakawa, 2006; Nestler and Hyman, 2010; Young et al, 2010; Jones et al, 2011; Canetta and Kellendonk, 2018). Nonetheless, animal models that recapitulate environmental influences (e.g., stress, drugs, infections, and socioeconomic status) on clinically identified risk-factor genes in the development of schizophrenia symptoms, including cognitive, positive, and negative symptoms, are able to provide insights into possible gene × environment interactions.…”
Section: Discussionmentioning
confidence: 99%
“…However, for neurological disorders, the complexity of the human brain, as compared to that of a rodent or even of a non-human primate, is extreme. For neuropsychiatric disorders, such as schizophrenia, common symptoms such as paranoid delusions and auditory hallucinations are uniquely human and make interpretation of results acquired from animal models particularly challenging ( Canetta and Kellendonk, 2018 ). Although imperfect, there are multiple available models of schizophrenia ( Winship et al, 2019 ), depression ( Planchez et al, 2019 ), and other neuropsychiatric ( Nestler and Hyman, 2010 ) as well as neurodegenerative disorders ( Dawson et al, 2018 ; Carta et al, 2020 ) that, to varying degrees, possess face validity (observed characteristics/symptoms that have clinical correlates in the human patient population), construct validity (key neurobiological/pathological bases of the human disorder), and/or predictive validity (expected pharmacological response to efficacious drugs currently used to treat the human disorder).…”
Section: Discussionmentioning
confidence: 99%
“…The challenges of translational research are perhaps most striking when considering disorders such as schizophrenia, where it seems difficult-though perhaps not impossibleto imagine how the aberrant psychological processing that gives rise to hallucinations and delusions could be modelled in non-human animals. This question is tackled directly by Canetta & Kellendonk [26], who assert that the historical limitations of animal models of mental health disorders in providing treatment leads have arisen because of a focus on developing models with face validity of behavioural symptoms, rather than models with construct validity of the underlying neurobiological differences contributing to altered psychological processing. By modelling potential causes of schizophrenia-genetic and environmental, including earlylife experiences-and measuring specific psychological processes, such as working memory, that have been shown to be impaired in patients with schizophrenia using translational tasks, it is possible to use the array of circuit-mapping and causal manipulations in rodents to provide insights into the clinical condition.…”
Section: Introductionmentioning
confidence: 99%